Determinación de parámetros elásticos de chapas - Coremberg, J.; Kohen, M.; Salomón, O. (Comisión Nacional de Energía Atómica; Argentina, 1972)
Fil: Coremberg, J. Comisión Nacional de Energía Atómica; Argentina